2017
DOI: 10.1111/ctr.12878
|View full text |Cite
|
Sign up to set email alerts
|

Early steroid withdrawal results in improved patient and graft survival and lower risk of post‐transplant cardiovascular risk profiles: A single‐center 10‐year experience

Abstract: Long-term use of steroids results in predictable secondary effects that can lead to increased morbidity and mortality. In this study, we present 10 years worth of data of early steroid withdrawal (ESW) immunosuppression consisting of mycophenolate, sirolimus, and tacrolimus. From 2003 to 2013, 563 kidney transplant recipients were weaned off steroids prior to discharge. We compared outcomes with that of our 65 historical controls maintained on steroids. We analyzed graft and patient survival and determined the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 25 publications
0
9
0
Order By: Relevance
“…Previous research supported that renal function 39 and graft survival 22 among recipients with ESW is comparable with among those with CSM. A randomized clinical trial data by Woodle et al 40 observed no difference of long-term death-censored graft failure and all-cause graft failure between ESW and CSM.…”
Section: Discussionmentioning
confidence: 83%
See 1 more Smart Citation
“…Previous research supported that renal function 39 and graft survival 22 among recipients with ESW is comparable with among those with CSM. A randomized clinical trial data by Woodle et al 40 observed no difference of long-term death-censored graft failure and all-cause graft failure between ESW and CSM.…”
Section: Discussionmentioning
confidence: 83%
“… 45 With advances in immunosuppression strategies, studies reported no differences in risk of acute rejection comparing ESW with CSM in combination with tacrolimus. 39 , 46 , 47 …”
Section: Discussionmentioning
confidence: 99%
“…Historically, the removal of steroids has been associated with the risk of precipitating AR [56,57]; however, long-term safety in terms of patient and graft survival has been satisfactory with early steroid withdrawal (ESW); as Rizzaari shows [58] in a 10 year followup of 1241 RT recipients with graft survival, showing similar death in living donor RT recipients with maintained with steroids (79 vs. 73%) and with even an better survival in deceased donor RT (80 vs. 67%) with a report in their survival analyses free of AR, similar between the groups with and without corticosteroids. Lopez Soler et al [59], similarly reported in a cohort undergoing ESW with a 10-year follow-up that showed better graft survival (p = 0.023), lower risk of mortality (0.23, p ≤ 0.011), and less graft failure (0.57, p = 0.026).…”
Section: Strategies For Removing Steroids From Immunosuppression In Kmentioning
confidence: 85%
“…Retrospective analysis of long term follow up (up to 15 years post-transplant) showed significantly lower rates of steroid associated complications. Furthermore, there was a significant improvement in patient and allograft survival[ 39 , 40 ].…”
Section: Discussionmentioning
confidence: 99%